Hybrid graphene oxide/carbon nanotubes reinforced cement paste: An investigation on hybrid ratio. (20th November 2020) - Du, Yuhang; Yang, Jian; Skariah Thomas, Blessen; Li, Lihui; Li, Huanyu; Nazar, Sohaib
Highlights: Hybrid graphene oxide (GO)/carbon nanotubes (CNTs) reinforced cement paste with various hybrid ratios were investigated. The dispersion properties of hybrid GO/CNTs were improved. The optimal hybrid ratio for compressive strength reinforcement was determined to be 3:2 (GO:CNTs). The 3D structure theory of hybrid GO/CNTs and the mechanism of reinforcement were also proposed. Abstract: This study reports the improved properties of hybrid graphene oxide (GO)/carbon nanotubes (CNTs) reinforced cement paste with various ratios between GO and CNTs (GO:CNTs). The dispersion level of hybrid GO/CNTs was evaluated by UV–vis spectroscopy, sedimentation experiment, zeta potential and dynamic light scattering analysis. Effects of various GO/CNTs ratio was analyzed by comparing the resulting fluidity, compressive and flexural strengths. The improving mechanism was confirmed by the morphology and pore structure analysis. The 3D structure theory of hybrid GO/CNTs and the interaction behavior between hybrid GO/CNTs and cement paste were also proposed. This study reveals that the hybrid GO/CNTs inherent dispersion mechanism showed stronger electrostatic repulsion and reduced particle size of the hybrid GO/CNTs. The hybrid GO/CNTs, with the dosage of 0.05% by weight of cement and the GO:CNTs mass ratio of 3:2, improved the compressive strength by 45.20%, which showed better reinforcing effects than the single addition of GO (28.00%) and CNTs (32.58%) with the same dosage respectively. It is worth noting that no evident synergistic effect was observed in the flexural case. In addition, the hybrid GO/CNTs decreased the fluidity performance up to 70% owing to the heat gained from the ultrasonication treatment and the viscosity of the hybrid GO/CNTs dispersion.